UJI KINERJA ALAT PENGERING HYBRID TIPE RAK PADA PENGERINGAN CHIP PISANG KEPOK - Ika Novita Sari; Warji .; Dwi Dian Novita (The University of Lampung, 2014)
Lampung Province was one of the banana production centers areas in Indonesia, one of them is kepok banana. Bananas don't have a long shelf life, so that it needs an alternative treatment to prolong shelf life so it can provide the value-of banana fruit. Drying system with hybrid is an alternative option. The purpose of this study is to test the performance of the hybrid dryer shelves type for drying banana chips. This research was conducted with three treatments, they were drying using solar energy, drying using electrical energy, and drying using solar energy and electricity, which was using 5 kg banana chips for each treatments. The three treatments of this research showed different results. It took 9 hours to drying banana chips until it reached the water content 10%-12% on drying using solar energy, while drying using electrical energy needed 11 hours, and 8 hours on drying using solar energy and electricity. Energy produced on drying using solar energy amounted to 55859,52 kJ, drying using electrical energy amounted to 27680,4 kJ and drying using solar energy and electricity was 64417,17 kJ. Keywords: Kepok banana chips, drying, the shelves type hybrid dryer